Inter-animal variability in the effects of C-type allatostatin on the cardiac neuromuscular system in the lobster Homarus americanus - Wiwatpanit, Teerawat (Company of Biologists, 2012)
Although the global effects of many modulators on pattern generators are relatively consistent among preparations, modulators can induce different alterations in different preparations. We examined the mechanisms that underlie such variability in the modulatory effects of the peptide C-type allatostatin (C-AST; pQIRYHQCYFNPISCF) on the cardiac neuromuscular system of the lobster Homarus americanus. Perfusion of C-AST through the semi-intact heart consistently decreased the frequency of ongoing contractions. However, the effect of C-AST on contraction amplitude varied between preparations, decreasing in some preparations and increasing in others. To investigate this variable effect, we examined the effects of C-AST both peripherally and centrally. When contractions of the myocardium were elicited by controlled stimuli, C-AST did not alter heart contraction at the periphery (myocardium or neuromuscular junction) in any hearts. However, when applied either to the semi-intact heart or to the cardiac ganglion (CG) isolated from hearts that responded to C-AST with increased contraction force, C-AST increased both motor neuron burst duration and the number of spikes per burst by about 25%. In contrast, CG output was increased only marginally in hearts that responded to C-AST with a decrease in contraction amplitude, suggesting that the decrease in amplitude in those preparations resulted from decreased peripheral facilitation. Our data suggest that the differential effects of a single peptide on the cardiac neuromuscular system are due solely to differential effects of the peptide on the pattern generator; the extent to which the peptide induces increased burst duration is crucial in determining its overall effect on the system.